AVALIAÇÃO DA IMPLEMENTAÇÃO DO PROJETO SIQ-CONSTRUTORAS DO PROGRAMA BRASILEIRO DA QUALIDADE E PRODUTIVIDADE DO HABITAT (PBQP-H) NO ESTADO DO RIO DE JANEIRO - Basile, Heloisa Helena G. (2004)
The productive sector from the civil engineering is of fundamental importance for the country, having influence in the socio-economical environment, constituting the biggest source of jobs and yield, possessing elevated and growing power to multiply the demand of suppliers, representing 15,5% of the national Gross Domestic Product. However, the segment of buildings is still distant of the technological level of development achieved by the other sectors and even of the other segments of civil construction, such as heavy duty construction and industrial assembly. Therefore, it is evident the importance of actions that contribute for its development, such as the one that is being implemented in national level, under coordination of the Cities Council, the Project SiQ Constructions to Quality Brazilian Program and Productivity of the Habitat PBQPH. However, in the State of the Rio de Janeiro the building companies number that adhered to the Program is still low in comparison with the number in other states, incoherent fact taking into consideration its financial and geographical situation. The study here presented intends to be a contribution for the institutions that participate on the evaluation programs development of conformity of the building companies management system, assuming as reference the Regiment of the System of Qualification of the PBQP-H. It aims to furnish the information acquuired from research with companies builders, necessary for the evaluation of the achieved goals and to that he its intends, to achieve in order to establish new strategic policies.